2022
DOI: 10.3390/jcm11030627
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Acylcarnitines and Amino Acids Are Associated with Liberation from Organ Support in Patients with Septic Shock

Abstract: Sepsis-induced metabolic dysfunction is associated with mortality, but the signatures that differentiate variable clinical outcomes among survivors are unknown. Our aim was to determine the relationship between host metabolism and chronic critical illness (CCI) in patients with septic shock. We analyzed metabolomics data from mechanically ventilated patients with vasopressor-dependent septic shock from the placebo arm of a recently completed clinical trial. Baseline serum metabolites were measured by liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In addition, pro-resolving mediators, including RvD2 and RvD3 (on day 3); RvE3 and RvD6 (on days 3 and 7); 17R-RvD1 (on day 7); 10S,17S-diHDHA, an isomer of protectin D1 (on days 1, 3 and 7); 17R-PD1 (on Day 3); 5-HEPE, a metabolite of eicosapentaenoic acid; and 14-HDHA, an intermediate in the synthesis of maresin 1 [ 137 ] (on days 0 and 3) were also significantly increased in septic patients with ARDS compared to those without [ 94 ] ( Figure 1 ). Another study investigating metabolic differences in mechanically ventilated septic patients found that proline, glycine, glutamine, methionine, acetylcarnitine and valerylcarnitine were associated with liberation from mechanical ventilation and vasopressors at 28 days [ 138 ].…”
Section: Metabolomics To Identify Prognostically Useful Clinical Phen...mentioning
confidence: 99%
“…In addition, pro-resolving mediators, including RvD2 and RvD3 (on day 3); RvE3 and RvD6 (on days 3 and 7); 17R-RvD1 (on day 7); 10S,17S-diHDHA, an isomer of protectin D1 (on days 1, 3 and 7); 17R-PD1 (on Day 3); 5-HEPE, a metabolite of eicosapentaenoic acid; and 14-HDHA, an intermediate in the synthesis of maresin 1 [ 137 ] (on days 0 and 3) were also significantly increased in septic patients with ARDS compared to those without [ 94 ] ( Figure 1 ). Another study investigating metabolic differences in mechanically ventilated septic patients found that proline, glycine, glutamine, methionine, acetylcarnitine and valerylcarnitine were associated with liberation from mechanical ventilation and vasopressors at 28 days [ 138 ].…”
Section: Metabolomics To Identify Prognostically Useful Clinical Phen...mentioning
confidence: 99%
“…Metabolic flexibility was shown to be an important characteristic of patients with sepsis for survival[ 27 ]. Plasma C2 Level was shown to be associated with multiple organ dysfunction, extubation, and freedom from vasopressors, or mortality in patients with sepsis[ 10 , 11 ]. In several studies, plasma short chain and medium chain acylcarnitines (C2, C3, C4, C5, C6, C8, C10) were significantly increased in the non-survivors[ 11 , 28 - 30 ] and only C2 was associated with all of these indices and 28-d mortality in sepsis[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies, however, suggested that glutamine decreases gastric colonization, infectious complications, and ICU length of stay [ 25 , 26 , 27 , 28 ]. Further confusing its role, elevations in glutamine along with proline, glycine, methionine, and two acylcarnitines were not only related to organ-support-free days but also chronic critical illness development [ 29 ].…”
Section: Introductionmentioning
confidence: 99%